Staphylococcus aureus and negative coagulase staphylococcus resistant to methicillin - Leonor Aties López; Gilberto Moya Jústiz; Milagros de la Caridad Milá Pascual; Ileana del Carmen Figueredo Acosta; Gardenia Brossard Alejo (Centro Provincial de Información de Ciencias Médicas, 2017)
A prospective study of 47 staphylococcus stumps coming from biological samples of the Microbiology Laboratory in "Saturnino Lora Torres" Teaching Clinical Surgical Provincial Hospital was carried out in Santiago de Cuba, from February to April, 2017, aimed at determining the frequency of staphylococcus resistant to methicillin. In the series, the highest number of isolations corresponded to the samples of secretions and catheter; also, the services with more notified isolations were Orthopedics and Surgery.  A high frequency of Staphylococcus aureus stumps and negative coagulase staphylococcus resistant to methicillin was observed.